Cross-Cultural Validation of the Polish Version of the ADI-R, Including New Algorithms for Toddlers and Young Preschoolers. - Chojnicka, Izabela; Pisula, Ewa (Child Psychiatry & Human Development, 2019)
Autism Diagnostic Interview-Revised (ADI-R) is one of the most widely used standardized diagnostic instruments for autism spectrum disorder (ASD). This article presents findings from the validation of the Polish version of the Autism Diagnostic Interview-Revised (ADI-R-PL), including new algorithms for toddlers and preschoolers. The validation group consisted of 125 participants: 65 with Autism Spectrum Disorder (ASD group) and 60 in the control group, including individuals with non-ASD disorders and typical development. The normalization group consisted of 178 participants, including 118 with ASD. The ADI-R-PL was found to have good psychometric properties. Confirmatory factor analysis supported both a bifactor structure and three-factor model. The study has generated preliminary information about the psychometric properties of the new algorithms for toddlers and young preschoolers. To the best of our knowledge, this paper is the first to propose new cutoffs in three ADI-R domains for a non-English-speaking population.